The NHS breast screening programme (pathology) EQA: experience in recent years relating to issues involved in individual performance appraisal. Issue 2 (27th January 2006) - Parham, D M; Coleman, D; Kodikara, S; Moss, S; Ellis, I O; Al-sam, S; Anderson, N; Bobrow, L; Buley, I; Connolly, C E; Dallimore, N S; Hales, S; et al.
Abstract : Background: The original role of the National Health Service breast screening programme (pathology) external quality assessment (EQA) scheme was educational; it aimed to raise standards, reinforce use of common terminology, and assess the consistency of pathology reporting of breast disease in the UK. Aims/Methods: To examine the performance (scores) of pathologists participating in the scheme in recent years. The scheme has evolved to help identify poor performers, reliant upon setting an acceptable cutpoint. Therefore, the effects of different cutpoint strategies were evaluated and implications discussed. Results/Conclusions: Pathologists who joined the scheme improved over time, particularly those who did less well initially. There was no obvious association between performance and the number of breast cancer cases reported each year. This is not unexpected because the EQA does not measure expertise, but was established to demonstrate a common level of performance (conformity to consensus) for routine cases, rather than the ability to diagnose unusual/difficult cases. A new method of establishing cutpoints using interquartile ranges is proposed. The findings also suggest that EQA can alter a pathologist's practice: those who leave the scheme (for whatever reason) have, on average, marginally lower scores. Consequently, with the cutpoint methodology currently used (which is common to several EQA schemes) there is the potential for the cutpoint to drift upwards. In future, individuals previously deemed competent could subsequently be erroneously labelled as poor performers. Due consideration should be given to this issue with future development of schemes.